Efficient dynamic bandwidth allocation for upstream EPON with global priority - Radzi N.A.M.; Din N.Md.; Al-Mansoori M.H.; Sadon S.Kh.; Majid Mohd.S.B.A. (2023)
An efficient dynamic bandwidth allocation (DBA) algorithm with global priority is proposed for upstream Ethernet passive optical network (EPON) in this paper. The algorithm is hierarchical and it ensures that the excessive bandwidth is allocated fairly according to the priority. The simulation is done using MATLAB by comparing Efficient DBA with global priority to Efficient DBA with local priority. The results show an improvement as high as 11% in terms of the bandwidth utilization and 46% in terms of the delay. 2010 IEEE.